Fostering Creativity in Higher Education Institution: A Systematic Review (2018-2022) - Setiamurti Astri; Kurniawati Farida (De Gruyter, 2024)
Several studies have stressed the necessity of fostering students' creativity in the twenty-first -century learning process, particularly at the higher educational level. This study synthesized the characteristics (country, study population, and field of education/subject), methods, and theoretical ground used to foster students' creativity in higher education research. Using the PRISMA 2020 as a guideline for writing a systematic literature review, two databases (ProQuest and Scopus) were searched for peer-reviewed, primary, and empirical research published in English between January 1, 2018, and October 15, 2022. A final selection of 28 studies that met the eligibility criteria were examined. The result showed that most of the studies reviewed were conducted on undergraduate students in developed industrialized East Asian countries and used surveys as the primary data collection method. Moreover, the grounding theories used in fostering creativity in higher education research were still scarce. This study showed that further research is needed to examine the mechanism for developing student creativity in higher education with more diverse samples, rigorous methods, and theoretical grounding.